Kajian Rencana Desain dan Analisisis Stabilitas Dinding Penahan Tanah Tipe Kantilever di Jalan Brigjend Abdul Manan Wijaya Kecamatan Pujon Kabupaten Malang - Sulastri, Yusiana ; Suhudi; Arianto, Andi Kristafy (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2018)
Retaining wall is an important component of the main building structure for building highways and other environmental related contoured land or land that has a different elevation. Briefly the retaining wall is a wall built to hold the soil mass above the structure or building is created. There are several types of retaining walls are often used in the building construction field include Gravity retaining walls, cantilever retaining walls, retaining walls kontrafort, and retaining walls butters, used in this study is a gravity type retaining wall using stone couple of times. The purpose of this study was to analyze the stability of the rolling force, shear and bearing capacity. The dimensions of the retaining wall are constructed with a length of (b) 17 meters and height (h) = 7.5 meters, base width (B) = 5 meters, normal waterfront condition without earthquake, stability to rolling force = 2.0> 1, 5 (safe), shear force = 2.3> 1.5 (safe), flood water conditions without seismic, stability to bolsters = 2.3> 1.5 (safe), shear force = 2.7> 1 , 5 (safe) and ground support force = 217.94 <qa = 7571,08 (safe). The retaining wall is planned to cost Rp.1.484,629,98 / m3.